K-SHARING SOLUTION FOR PUBLISHING ORGANISATION USING WEB PORTAL - MAZLAN, MOHD HANIF (Universiti Teknologi Petronas, 2011)
The essential business knowledge process in a publishing company generally comes from personnel that are involved in the publishing workflow. If the personnel or individual expert in the certain area of knowledge, the person tends to get high intention from upper management. Knowledge as part of personnel asset, make the personnel or individuals be inclined to share their knowledge. Because of that, there are no platforms or tools that had been created to allow knowledge sharing process in the related industry. Hence, this research is performed to recognize or discover and deal with knowledge audit. The knowledge audit is the all important first major phase or step of a knowledge management initiative, and is used to provide a sound investigation into the company or organisation's knowledge health. The knowledge audit provides an evidence-based evaluation of where the organisation needs to spotlight its knowledge sharing efforts. It can expose the organisation's knowledge sharing needs, strengths, weaknesses, opportunities, threats and risks. The portal was developed using content management system (CMS), Joomla as the editor and PHP language as the programming script.